Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Covid-19 (Kajian Persepsi Orang Tua Tentang Efektivitas Pembelajaran Berbasis Online Di Mis Al Fajar Sei Mencirim) - Darwis Margolang; Suci Safitri; Rusmayani Rusmayani; Agusti Puspita Sari (Yayasan Rahmat Islamiyah, 2020)
This study aims to analyze (1) Modification of learning during the Covid-19 pandemic, (2) Parents' perceptions of effectiveness, (2) the impact of parental perceptions on student learning outcomes. Parents' perceptions regarding the effectiveness of online learning do appear to be greater in the statements of parents who think that online learning is not effective, arguing that online learning presents many limitations both in interaction and assessment of learning. This research was conducted at MIS Al Fajar Sei Mencirim. The method used is a qualitative method with a descriptive study approach. The results of the study show that learning modifications during the Covid 19 pandemic include online discussion learning, assignment-based online learning, and parent mentoring-based online learning. The impact of parents' perceptions on learning is that there is a gap between parents and the school, especially teachers, such as reluctance to participate in learning programs, even reluctant to assist children in learning. Keywords: Learning, Islamic Education, Perseption, parent